Differences in hospitalisation between peritoneal dialysis and haemodialysis patients. (15th February 2022) - van Eck van der Sluijs, Anita; Bonenkamp, Anna A.; van Wallene, Vera A.; Hoekstra, Tiny; Lissenberg‐Witte, Birgit I.; Dekker, Friedo W.; van Ittersum, Frans J.; Verhaar, Marianne C.; van Jaarsveld, Brigit C.; Abrahams, Alferso C.
Abstract: Background: Dialysis is associated with frequent hospitalisations. Studies comparing hospitalisations between peritoneal dialysis (PD) and haemodialysis (HD) report conflicting results and mostly analyse data of patients that remain on their initial dialysis modality. This cohort study compares hospitalisations between PD and HD patients taking into account transitions between modalities. Methods: The Dutch nOcturnal and hoME dialysis Study To Improve Clinical Outcomes collected hospitalisation data of patients who started dialysis between 2012 and 2017. Primary outcome was hospitalisation rate, analysed with a multi‐state model that attributed each hospitalisation to the current dialysis modality. Results: In total, 695 patients (252 PD, 443 HD) treated in 31 Dutch hospitals were included. The crude hospitalisation rate for PD was 2.3 ( ± 5.0) and for HD 1.4 ( ± 3.2) hospitalisations per patient‐year. The adjusted hazard ratio for hospitalisation rate was 1.1 (95%CI 1.02–1.3) for PD compared with HD. The risk for first hospitalisation was 1.3 times (95%CI 1.1–1.6) higher for PD compared with HD during the first year after dialysis initiation. The number of hospitalisations and number of hospital days per patient‐year were significantly higher for PD. The most common causes of PD and HD hospitalisations were peritonitis (23%) and vascular access‐related problems (33%). Conclusion: PD was associated with higher hospitalisation rate, higher risk for first hospitalisation and higher number of hospitalisations compared with HD. Since the PD hospitalisations were mainly caused by peritonitis, more attention to infection prevention is necessary for reducing the number of hospitalisations in the future.